2013
DOI: 10.11646/zootaxa.3669.3.2
|View full text |Cite
|
Sign up to set email alerts
|

An introduction to the systematics of <i>Akodon orophilus</i> Osgood, 1913 (Rodentia: Cricetidae) with the description of a new species

Abstract: The genus Akodon is one of the most species-rich rodent lineages in South America. In Peru, this genus contains 14 species subdivided in two groups: aerosus and boliviensis. Akodon orophilus Osgood, 1913 (Rodentia: Cricetidae) is a member of the Akodon aerosus group that inhabits the northern Peruvian montane forest, but is poorly characterized and its distri-bution is vaguely known. We review the status of the species based on morphology, morphometric and karyology, and compared with all members of the Akodon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 20 publications
1
17
0
8
Order By: Relevance
“…Our new records for Peru add one more genus and three species to the country reaching to 541 mammal species in Peru (Pacheco et al, 2009;Lim et al, 2010;Velazco et al, 2010aVelazco et al, , 2010bGregorin & Almeida, 2010;Gutiérrez et al, 2010;Mantilla-Meluk & Baker, 2010;Díaz, 2011;Velazco & Cadenillas, 2011;Hice & Velazco, 2012;Larsen et al, 2012;Medina et al, 2012;Jiménez et al, 2013;Marsh, 2014;Medina et al, 2014;Pacheco et al, 2014;Rengifo et al, 2014;Velazco et al, 2014;Zeballos et al, 2014;Patton et al, 2015;Hurtado & Pacheco, 2015;Vermeer & Tello-Alvarado, 2015). That show the importance of conduced Flora and Fauna Monitoring Programs for knowing better the diversity of Peruvian mammals in Peru as a whole and in Pampas del Heath in particular.…”
Section: Distributionmentioning
confidence: 74%
“…Our new records for Peru add one more genus and three species to the country reaching to 541 mammal species in Peru (Pacheco et al, 2009;Lim et al, 2010;Velazco et al, 2010aVelazco et al, , 2010bGregorin & Almeida, 2010;Gutiérrez et al, 2010;Mantilla-Meluk & Baker, 2010;Díaz, 2011;Velazco & Cadenillas, 2011;Hice & Velazco, 2012;Larsen et al, 2012;Medina et al, 2012;Jiménez et al, 2013;Marsh, 2014;Medina et al, 2014;Pacheco et al, 2014;Rengifo et al, 2014;Velazco et al, 2014;Zeballos et al, 2014;Patton et al, 2015;Hurtado & Pacheco, 2015;Vermeer & Tello-Alvarado, 2015). That show the importance of conduced Flora and Fauna Monitoring Programs for knowing better the diversity of Peruvian mammals in Peru as a whole and in Pampas del Heath in particular.…”
Section: Distributionmentioning
confidence: 74%
“…Así mismo, se encontraron diferencias en algunas variables de la muestra global con respecto a la clase de edad 2; por lo cual se podría sospechar de formas no adultas en dicha clases de edad y apoyaría resultados anteriores (Jiménez et al 2013, Prado & Percequillo 2011, Patton et al 2000. El análisis global también reveló una ausencia de dimorfismo sexual en la especie según lo esperado.…”
Section: Discussionunclassified
“…Así mismo dicha diferenciación se puede encontrar en diversos estudios; Jiménez et al (2013), analizaron más de 100 individuos de Akodon orophilus de los departamentos Amazonas, San Martin y Huánuco en Perú, utilizando 19 medidas cráneo -dentales y análisis de MANOVA para comparar las distintas clases de edades y ambos sexos; los autores encontraron que las clases de edad 4 y 5 eran las únicas que no presentaron diferencias significativas a nivel de las variables analizadas.…”
Section: Manovaunclassified
“…Other species are known to have ranges similar to P. pearsoni including the akodontines Akodon nov. sp. (Pacheco et al 2009) and Akodon mollis (Jiménez et al 2013), and the thomasomyines Thomasomys praetor and T. pyrrhonotus (Pacheco in press). The concordance of these ranges of species from different tribes suggest that the western Andean Cordillera in Northern Peru might represent a center of endemism for rodents and likely other taxa.…”
Section: Discussionmentioning
confidence: 99%
“…In rodents, for example, Akodon josemariarguedasi was recently described (Jiménez et al 2013); Oecomys paricola was reported for first time for the country (Hice and Velazco 2012); Akodon baliolus is now recognized as full species (Pacheco et al 2011;Coyner et al 2013), as are A. surdus (Coyner et al 2013) and Oxymycterus juliacae (Pacheco et al 2011). Rhipidomys latimanus was also added to the country's fauna (Tribe 1996, Tribe in press).…”
Section: Wwwmastozoologiamexicanaorg 493mentioning
confidence: 99%